El exilio de Clorinda Matto de Turner - Martínez Hoyos, Francisco (CUADERNOS KÓRE, 2011)
After the "coup d’état" that overthrew president Cáceres in 1895, the novelist Clorinda Matto, who was one of his most significant supporters, left Perú. After being to Chile, she definitively established herself in Buenos Aires. There, she founded the "Búcaro Americano" magazine. This article explores her long and productive exile, the least handled period of her biography. In her writings, Clorinda continued with her defense of feminine emancipation. Nonetheless, she did it from a more conservative political view. Little time before her death, she was involved in an interesting European tour, in which she contacted with other writers and knew about many realities related with women’s world.